Degradation of acid red 27 by the recombinant flavin reductase - Abdul Wahab, Mohd. Firdaus; Abdul Rashid, Noor Aini; Mohd. Yusoff, Abdull Rahim (2006)
This paper focuses on the degradation of azo compound C.I. Acid Red 27 (AR27, amaranth) by the recombinant enzyme flavin reductase (FRE) from Citrobacter freundii strain A1. The enzyme was obtained via re-transformation of recombinant plasmid pET-43.1c(+)freBP containing the flavin reductase gene (fre) into E. coli NovaBlue. The plasmid was subsequently transformed into E. coli BL21(DE3)pLysS for overexpression of FRE fusion protein. Prior to that, the stability of fre gene was first verified using PCR amplification and also sequencing of the nucleotides and consequently compared with the original fre gene sequence from C. freundii A1. The protein was expressed as inclusion bodies and was isolated and refolded in order to obtain a properly-folded and active flavin reductase. The activity and the protein yield were monitored using a modified flavin reductase assay and Bradford assay respectively. The active enzyme was further subjected to the degradation of AR27 and the degradation profile was constructed.